Formyl peptide receptor 1 suppresses gastric cancer angiogenesis and growth by exploiting inflammation resolution pathways. (3rd April 2017) - Prevete, Nella; Liotti, Federica; Illiano, Anna; Amoresano, Angela; Pucci, Piero; de Paulis, Amato; Melillo, Rosa Marina
ABSTRACT: Chronic inflammation can result from inadequate engagement of resolution mechanisms, mainly accomplished by specialized pro-resolving mediators (SPMs) arising from the metabolic activity of lipoxygenases (ALOX5/15) on ω-6 or ω-3 essential polyunsaturated fatty acids (PUFA). We previously demonstrated that formyl peptide receptor 1 (FPR1) suppresses gastric cancer (GC) by inhibiting its inflammatory/angiogenic potential. In this study, we asked whether FPR1 exploits inflammation resolution pathways to suppress GC angiogenesis and growth. Here, we demonstrate that genetic or pharmacologic modulation of FPR1 in GC cells regulated ALOX5/15 expression and production of the SPMs Resolvin D1 (RvD1) and Lipoxin B4 (LXB4). SPM treatment of GC cells abated their angiogenic potential. Genetic deletion of ALOX15 or of the RvD1 receptor GPR32 increased the angiogenic and tumorigenic activity of GC cells thereby mimicking FPR1 loss. Deletion/inhibition of ALOX5/15 or GPR32 blocked FPR1-mediated anti-angiogenic activities, indicating that ALOX5/15 and GPR32 are required for FPR1's pro-resolving action. An ω-3- or ω-6-enriched diet enforced SPM endogenous production in mice and inhibited growth of shFPR1 GC xenografts by suppressing their angiogenic activity. These data implicate that FPR1 and/or pro-resolving pathway components might be used as risk/prognostic markers for GC; ω-6/3-enriched diets, and targeting FPR1 or SPM machinery may be exploited for GC management.